A holistic evaluation of the e-procurement website by using a hybrid MCDM methodology. (2013) - Kabak, Mehmet; Burmaoğlu, Serhat
Governments strive to enhance electronic applications in an attempt to take advantage of the benefits of the internet. The most important application of the e-government applications is electronic Public Procurement (e-PP) and it can be defined as the purchasing of goods and services via internet. Like other developed and developing countries, Turkey also shifted the public procurement system through electronic means. Therefore, this study is aimed to develop an evaluation model for web interface of the e-PP which is called EKAP. While developing the model, Decision Making Trial and Evaluation Laboratory (DEMATEL), Analytic Network Process (ANP) and fuzzy set theory are used. As a result, standardisation, links, reliability and navigability are found as the most important urgent need for improvement.